MANAGING ASSISTANCE IN THE FIELD OF SOCIAL INCLUSION ADDRESSED TO YOUNG PEOPLE FROM MIGRANT FAMILIES AT THE EUROPEAN UNION LEVEL - Dybowska, Agnieszka (Management and Administration Journal, 2024)
Youth migration can be considered in many aspects. More and more young people from third countries are moving to European countries on their own or with their parents, sometimes at a very young age or even in childhood. At the same time, more and more young Europeans are becoming mobile across the continent. In terms of public policy for youth, it should be noted that students and pupils from a migrant background often struggle with difficulties in adapting to new learning conditions. Social inclusion of all young people, including those with migrant backgrounds, is one of the priorities of EU public policies in the youth field. Nowadays, social inclusion is largely based on activities that do not allow for digital exclusion, because modern education is very closely related to modern technologies. The instruments for implementing public policy for youth involve various programs funded by the European Union. These programs play a very important role in the process of social inclusion of young people from migrant families. As a result of the research, using the method of institutional and legal analysis, it was concluded that the key recommendation is that all activities addressed to young people from migrant families should enable them to function well in youth communities.